Win the Leadership Game Every Time Nine Invaluable Laws to Magnify Your Success. - Nanjiani, Payal (Milton : Productivity Press, 2022)
Far away in the jungle of Africa every morning a deer wakes up and decides to run faster than the fastest lion in that jungle. In the same jungle every morning a lion wakes up and decides to run faster than the fattest deer in that jungle. Both the deer and the lion wake up with the aim to win. The deer wants to win to save its life. The lion wants to win to satisfy its hunger. They each have their reason to win. They are in the game for winning. None of them know whether or not they will win, yet they decide each day to win. Are you in the leadership game to win or are you just a player in the game? Do you wake up each morning deciding to win or do you wake up to go to work and simply complete your tasks? There is a huge difference between going to work to win and going to work to just be in the game. It is this difference that decides where each of us is on the growth ladder and where we will be. Those who are here to just be in the game are very concerned about their paycheck and job security. They fear taking risks and are overly cautious. These people view the game as an "I win, you lose" proposition. But those leaders who play to win, do whatever is necessary to move things forward. They're not reckless, but proactive. They make the call that they fear. They have difficult conversations. They deal with the tricky issues that may put their outcomes at risk if things go south on them. These are the people who wake up each morning with the will to win. They know that winning has nothing to do with power, status quo, position, or playing corporate politics. Winning is purely about being relentless and moving ahead in the game by focusing on your improvement and on the well-being of others. Winning is about having faith in yourself and in your abilities. Almost 75% of the people in the workforce get stuck at the mid-management level in the organization. These people have the best skills and abilities, yet aren't able to move the needle significantly. This is because they don't know what it takes to win and get unstuck. The purpose of the nine crucial laws described in this book is to guide you to methodologically win the leadership game. There are two ways of winning the game. One, by playing dirty corporate politics, bumping others to reach your goal, thinking solely about your growth, and being selfish. Another and better way is to work on transforming yourself so you improve in the game each day. The rules of business are changing. The game is evolving with speed. New markets are emerging. A new generation of workforce is entering the game. We have entered into a digitally transformed world. The new leadership game cannot be played with old rules and competencies. Working with some great leaders has shown me how a leader can move with agility, speed and flexibility to revamp the organization when faced with a business crisis. A leaders decisive and bold actions and their rapid and insightful response to crisis demonstrated the value of speed and serenity in setting a new course for their company. What are the new rules and competencies? How do we play and win the leadership game, every time?
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Management; Leadership; Success in business; Executive ability